The Use of Song Lyrics for Teaching Vocabulary at Smp Amal Mulya Tawangmangu in 2014/2015 Academic Year - Lelyana Kisworo Putri, Adhe; , Drs. Djoko Srijono, M.Hum; , Dra. Muamaroh, M.Hum, Ph.D (2015)
This study aims at describing the use of song lyrics for teaching vocabulary at SMP Amal Mulya Tawangmangu. The researcher wants to know the procedure of using song lyrics based on students' textbook the 2013 curriculum. The type of the research is descriptive research. The subject of this research is the English teacher and the seventh grade students of SMP Amal Mulya Tawngmangu. The research questions of this research paper are the procedure of using song lyrics based on the 2013 curriculum and the problems faced by teacher during using song lyrics for teaching vocabulary. The techniques of collecting data were observation, interview and document analysis. The researcher used Miles and Huberman's theory cited in Sugiono (2010:337) in analyzing the data. After collecting the data, the researcher reduced the data, displayed the data and verified the data. The findings showed that the song lyrics are used for two purposes. The first purpose is for teaching vocabulary. The second purpose is for icebreaking. The procedure of using song lyrics for teaching vocabulary is the teacher prepares video or audio based on the students' textbook. Then teacher plays video or audio for the students 2 or 3 times to make the students familiar with new words in the song. The teacher and the students sing a song together 2 or 3 times. The teacher guides the students to learn the meaning of new words deeply and clearly. The teacher gives the students worksheet. The teacher and the students corrected the worksheet. Finally the teacher and the students sing a song again. The problem faced by the teacher during the use of song for teaching vocabulary is the students do not know the meaning of vocabulary in the song.